Anaesthesia, Pain, Intensive Care and Emergency Medicine — A.P.I.C.E. Proceedings of the 18th Postgraduate Course in Critical Care Medicine Trieste, Italy — November 14–17, 2003 Volume II - Gullo, Antonino (Springer Milan, 2004)
Continuous update in critical care medicine is a real challenge due to the growing dimensions of its contents; these elements are the result of new research acquisitions, and of those clinical situations where the physician is able to intervene at a given moment, with the use of effective prevention techniques. They are also the result of new technologies able to define complex sub-clinical diagnostic aspects; lastly, they are the result of effective therapeutic techniques available, and of treatment strategies able to influence radically and positively the patient's clinical course. Critical care medicine is playing a key role in the most advanced environments, as it represents a cross-sectional field of action, involving several specialties, such as anesthesiology, general medicine, surgery, pediatrics
Keywords: Anesthesiology; Intensive / Critical Care Medicine; Critical care medicine; Konferenzschrift